Recommendations for adult and paediatric cardiologists on obtaining additional qualification in “Adults with Congenital Heart Disease” (ACHD) - Hess, John; Bauer, Ulrike; Haan, Fokko de; Flesh, Julia; Gohlke-Baerwolf, Christa; Hagl, Siegfried; Hofbeck, Michael; Kaemmerer, Harald; Kallfelz, Hans Carlo; Lange, Peter E.; Nock, Hermine; Schirmer, Karl Robert; et al. (International journal of cardiology, 2011)
Background - The number of adult congenital heart disease (ACHD) patients will be larger in the medium to long term than that of children and adolescents with congenital heart disease. The present structures for the medical care of ACHD patients are not sufficient and need to be improved. Therefore the Task Force aimed at developing recommendations for adult and paediatric cardiologists to acquire the additional qualification “Adults with Congenital Heart Disease” (ACDH). - Methods - The members of the interdisciplinary Task Force were selected on the basis of their special clinical, scientific and organisational expertise. The leading author submitted a draft version, which was revised by a sub-group of the interdisciplinary Task Force. It was subsequently agreed upon and re-circulated by all the members of the Task Force. The recommendations were then presented to the relevant committees of all participating associations and groups and approved following detailed discussion. - Results - A training programme for acquiring an additional qualification in the treatment of adults with congenital heart disease was created successfully. - Conclusions - The medical care of adults with congenital heart disease is a sub-speciality in the border area between adult cardiology and paediatric cardiology. ACHD cardiologists are to be specially trained experts with appropriate knowledge and special skills and experience in the diagnosis and therapy of congenital heart disease in adults. ACHD cardiologists should be able to recognise and treat problems that occur in adulthood in connection with congenital heart disease.